Anesthesia for interventional radiology. Issue 7 (12th May 2014) - Landrigan‐Ossar, Mary; McClain, Craig D.; Soriano, Sulpicio
Summary Pediatric patients in the neurointerventional radiology setting pose the dual challenges of caring for relatively sick patients in the outfield environment. For safe and successful practice, the anesthesiologist must not only understand the nuances of pediatric anesthesia and the physiologic demands of the cerebral lesions. They must also help maintain a team‐based approach to safe, compassionate care of the child in this challenging setting. In this review article, we summarize key aspects of success for several of these topics.